Quantum mechanics : non-relativistic theory - Landau, L. D. 1908-1968; Lifshit︠s︡, E. M. (Butterworth Heinemann, 1977)
This edition has been completely revised to include some 20% of new material. Important recent developments such as the theory of Regge poles are now included. Many problems with solutions have been added to those already contained in the book.
Translation of: Kvantovai︠a︡ mekhanika.
Reprinted 1981, 1985, 1987, 1989, 1991 (with corrections), 1994, 1998, 1999, 2000, 2002, 2003, 2005 (twice).
Keywords: Nonrelativistic quantum mechanics.; elektronické knihy; electronic books